Análise espacial do desenvolvimento econômico das microrregiões do oeste do Paraná - Oliveira, Marines Rute de (2014)
On this dissertation the economic development concept that was used takes place through the analysis of social and economic data, in which it is verified if the growth is related to the economic development of a place, coming from the principle that the development is due to the growth interconnected with the improvement in the quality of life of the population. Along with the new challenges that have been presented to the economy of the state of Paraná, it is essential to evaluate the technical, financial and political possibilities of reassuring the role of the local state as a correcting agent of interregional and social inequalities and to rethink the designs, the objectives and the orientation of social policies in order to make them innovative when facing the transformations that are occurring in society. Thus it is necessary to know how the economic development is distributed in the microregions of Cascavel, Toledo and Foz do Iguaçu, that form the western region of Paraná. In this sense the objective of this study was to analyze the economic development of municipalities of the microregions in the west of Paraná, verifying the determiners of the development level and classifying them according to the degree of economic development, conducting as well an exploratory analysis of spatial data. In using the technique of multivariate statistic, the factor analysis, an indicator was elaborated, the Index of Gross of Development to the 50 analyzed municipalities. It was verified, also, the spatial dependence of the calculated index. The results indicate, from the factor analysis applied to the model for the years of 2002 and 2012 the extraction of 5 factors that explain, jointly, 76,31% of total variance of the selected variables. In which the factor 1 is directly related to the quality of life of the population, factor 2 is related to urbanization and economic development, factor 3 is directly related to education, factor 4 is directly related to unemployment and income distribution and factor 5 is correlated to the GAV of services. The gross development index, which is the weighted average of each one of the 5 found factors to the years of 2002 and 2012, was of 3.27 and 6.17, respectively. Along with the classification of the analyzed municipalities it was possible to observe that only three municipalities were able to be classified with high development in 2002 and in 2012. Only 9 municipalities in 2002 achieved an average classification and, in 2012, this number increased to 19. The majority of municipalities got a classification of development considered to be low in 2002 (39) and, in 2012, this number stood at just (28). It was verified that the Index of Economic Development does not suffer influence of the spatial proximity, as the estimates that detect the spatial autocorrelation were not statistically significant. It was noted that there were no differences, in statistical terms, of the IBD in the majority of the studied municipalities, where through the cartograms few outliers were detected. As for the cluster formation, it was observed that the majority of municipalities have IBD that does not statistically differ from the average of the IBD from the western region. These results let it show that there is a homogeneity level in the region, not confirming the hypothesis of the research that the economic development was occurring in a different way among its municipalities.